Study on Oil Palm Fresh Fruit Bunch Bruise in Harvesting and Transportation to Quality - Krisdiarto, Andreas Wahyu; Sutiarso, Lilik (UI Scholars Hub, 2016)
There are losses of production due to oil palm field’s material handling. Activities that may raise the losses are harvesting and transportation, which may cause bruise and damage to fruit. This research was aimed to learn the bruise of fresh fruit bunch (FFB) phenomenon in harvesting and transportation. Method used in this research was measuring the bruise area resulted by FFB falling when harvested, loading (throwing up) FFB to truck bin, and transporting using truck. These data, coupled with weight of bruised fruit, were calculated to get FFB bruise index. Each FFB bruise index is related to potential free fatty acid (FFA) value. FFA is one of important quality indicator of crude palm oil. The harvesting was conducted at mineral land and peat land, and the loading and transportation was conducted using wooden board truck and dump (iron board) truck. There was a difference between bruise index and FFA of FFB fall on mineral and on peat land. FFA of mineral land harvesting was 2.19% while of peat land was 1.27%. It was obvious that fruit quality degradation was higher when FFB positioned at the bottom of bin truck layer rather than at the top. FFA of truck bin bottom layer was 2.79% while of top layer was 0.64%. It was found that there was a cumulative bruise on FFB within material handling, start from harvesting, loading up to truck bin, and transporting from field to loading ramp.